Application of Yospan as a Programmatic Method for Spatial Experience and Flexibility in the Central Marketplace of Manokwari - Asterica Deviana Ardhikawati; Purwanita Setijanti (Jurnal Sains dan Seni ITS, 2017)
As a coastal city, Manokwari’s coastline is where the central development grows, one of which is the Sanggeng Marketplace. This central market area is a vital system in the city. Yet, it lacks the development required to accommodate future growth and risks. The issue at hand discusses the marketplace’s position as a commercial and recreational space and how both can be integrated into a space that caters to the bright, multicultural citizens of the city of Manokwari. The design proposed in this final project accommodates the merging of both commercial, recreational, and social spaces in a single marketplace through spatial flexibility and the programming of spatial experiences. By designing a marketplace that not only delivers flexible spatial functions but also reflects the vibrancy and provides a spatial experience, the Sanggeng Market can exist as a central marketplace that can significantly further benefit the city, both economically and socially.